Technological culture and vulnerability to psychic trauma - Julio Peres; Ana Carolina Sanchez Dias; Ana Maria Vilar Suassuna; Márcio Augusto de Almeida; Simone Álvares Guedes; Gisela Paraná Sanches (O Mundo da Saúde)
The development of information and communication technologies (ICTs) in the last few decades had intense effects in many aspects of social and individual life, creating other human ways of thinking, feeling and acting in a new kind of society influenced by technological culture. The so-called virtual world is ever more attractive due to the quality and the amount of technological information with high resolution and a myriad of lively colors, which no doubt seduce users by means of excitation provoked by sensorial stimuli. On the other hand, parents are ever busier due to pressures for a good performance in a cultural context marked by haste and tend to ignore the isolation of their apparently entertained children, but with affective disturbances caused by the problematic use of ICTs. Researchers disclose new problems associated to the chaotic and constant movement of virtual information, which causes emotional illiteracy and consequently vulnerability to psychic trauma due to cognitive processing deficits. Mental health professionals must be aware of potential comorbidities associated to the unregulated use of ICTs, as they must counsel and guide about the necessity of more participation of parents, family members and educators in the reduction and prevention of traumatogenic risks to youths influenced by the prevalent technological culture in urban centers.